2015
DOI: 10.1103/physrevb.92.035303
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high negative electron affinity of diamond via magnesium adsorption

Abstract: We report large negative electron affinity (NEA) on diamond (100) using magnesium adsorption on a previously oxygen-terminated surface. The measured NEA is up to (−2.01 ± 0.05) eV, the largest reported negative electron affinity to date. Despite the expected close relationship between the surface chemistry of Mg and Li species on oxygen-terminated diamond, we observe differences in the adsorption properties between the two. Most importantly, a high-temperature annealing step is not required to activate the Mg-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
0
35
0
3
Order By: Relevance
“…As noted above, the germanium termination achieves a maximum coverage below 1 ML, and thus it is reasonable to consider whether the surface carbon which has not bonded with germanium remains vulnerable to oxidation. Oxidation of the bare (100) diamond surface generates C1s components to high binding energy of the bulk diamond peak . For the C1s spectra shown in Figure , while there is some change in the distribution of spectral weight to the high binding energy side of the bulk diamond component, we do not attribute this to the oxidation of surface carbon based on the following argument.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…As noted above, the germanium termination achieves a maximum coverage below 1 ML, and thus it is reasonable to consider whether the surface carbon which has not bonded with germanium remains vulnerable to oxidation. Oxidation of the bare (100) diamond surface generates C1s components to high binding energy of the bulk diamond peak . For the C1s spectra shown in Figure , while there is some change in the distribution of spectral weight to the high binding energy side of the bulk diamond component, we do not attribute this to the oxidation of surface carbon based on the following argument.…”
Section: Resultsmentioning
confidence: 88%
“…Extending the range of available terminations offers new possibilities for developing diamond surfaces as a technologically relevant platform. Typical elemental terminations include hydrogen, oxygen, nitrogen, and fluorine; more complex terminations based around metal‐oxides have been developed, as well as biologically relevant organic functionalizations . While the chemically inert nature of diamond is considered a benefit for a large number of applications, Raymakers et al have shown that forming a covalent surface functionalization with diamond is complicated by the stability and chemical passivity of the diamond surface.…”
Section: Introductionmentioning
confidence: 99%
“…Низкопороговая АЭ обусловлена следующими эффектами: пористостью и проникновением поля, большим числом поверхностных уровней и отрицательным зарядом на поверхности кластеров, малым электронным сродством, которое при легировании может стать отрицательным. Отрицательному электронному сродству в алмазных кластерах посвящены работы [53,54,[76][77][78][79][80][81][82]. Рассматривается допирование такими элементами, как Li, Mg, Ag, N, Ni, Ag.…”
Section: заключениеunclassified
“…Рассматривается допирование такими элементами, как Li, Mg, Ag, N, Ni, Ag. В частности, в [78] допировании Li достигнуто отрицательное сродство −1.47, а в [82] при допировании Mg экстремально высокое отрицательное электронное сродство −2.1 eV. По-видимому, основными проблемами получения больших плотностей тока из таких АГП являются удержание и охлаждение кластеров, чему может способствовать сетка, в качестве которой может служить графен.…”
Section: заключениеunclassified
“…В отличие от адсорбции металлов на металлах [17] адсорбция металлов на полупроводниках изучена слабо, так что авторам не удалось найти данных даже по энергии адсорбции бария на кремнии и алмазе, хотя некоторые данные по этим (или близким) адсорбционным системам имеются (см. [18,19] и [20,21]). Обратимся поэтому для сравнения к адсорбции цезия.…”
unclassified